Animal models for HIV/AIDS research - Hatziioannou, Theodora (Nat Rev Microbiol, 2012)
The AIDS pandemic continues to present us with unique scientific and public health challenges. Although the development of effective antiretroviral therapy has been a major triumph, the emergence of drug resistance requires active management of treatment regimens and the continued development of new antiretroviral drugs. Moreover, despite nearly 30 years of intensive investigation, we still lack the basic scientific knowledge necessary to produce a safe and effective vaccine against HIV-1. Animal models offer obvious advantages in the study of HIV/AIDS, allowing for a more invasive investigation of the disease and for preclinical testing of drugs and vaccines. Advances in humanized mouse models, non-human primate immunogenetics and recombinant challenge viruses have greatly increased the number and sophistication of available mouse and simian models. Understanding the advantages and limitations of each of these models is essential for the design of animal studies to guide the development of vaccines and antiretroviral therapies for the prevention and treatment of HIV-1 infection.